2017
DOI: 10.1007/s13205-017-0746-1
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory power of rbcL barcode locus for authentication of some of United Arab Emirates (UAE) native plants

Abstract: DNA barcoding of United Arab Emirates (UAE) native plants is of high practical and scientific value as the plants adapt to very harsh environmental conditions that challenge their identification. Fifty-one plant species belonged to 22 families, 2 monocots, and 20 eudicots; a maximum number of species being legumes and grasses were collected. To authenticate the morphological identification of the wild plant taxa, rbcL and matK regions were used in the study. The primer universality and discriminatory power of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
3
22
0
1
Order By: Relevance
“…This may possibly be linked to sample contamination or a deficiency on the part of the rbcL resolution. The identified genetic distances (0.5000 ± 0.4770 -5.0560 ± 2.5760) based on K2P model regarding the inter-groups were in agreement with the previous works of other researchers in yams [24] [54] and in authentication of native plants [60]. High genetic diversity indices were obtained from between group calculations, producing 5.0560 ± 2.5760 with the highest in two combined groups (groups VI and VII) and this demonstrates higher interspecific diversity than intraspecific one within the yam accessions as obtained in an earlier report involving ornamental plants with interspecific value of 3.080 [61].…”
Section: Discussionsupporting
confidence: 90%
“…This may possibly be linked to sample contamination or a deficiency on the part of the rbcL resolution. The identified genetic distances (0.5000 ± 0.4770 -5.0560 ± 2.5760) based on K2P model regarding the inter-groups were in agreement with the previous works of other researchers in yams [24] [54] and in authentication of native plants [60]. High genetic diversity indices were obtained from between group calculations, producing 5.0560 ± 2.5760 with the highest in two combined groups (groups VI and VII) and this demonstrates higher interspecific diversity than intraspecific one within the yam accessions as obtained in an earlier report involving ornamental plants with interspecific value of 3.080 [61].…”
Section: Discussionsupporting
confidence: 90%
“…The NJ method in reconstructing kinship relationships based on the proximity of the evolutionary distance that occurs, indicated by the value of the kinship distance matrix among individuals. The evolutionary distance can be considered as genetic distance which shows the evolutionary rate is different for each cultivar (Maloukh et al, 2017). The lower the matrx value the closer kinship relationship and vice versa, the higher kinship matrix value, the farther the kinship distance between the two cultivars in the cladogram.…”
Section: Results Rbcl Sequence Analysismentioning
confidence: 99%
“…This finding was contrary to previous studies that suggested using the rbcL barcode for the identification of rare desert plants. For example, Maloukh et al (2017) used rbcL and matK loci for a group of 51 native plants (belonging to 22 families) from the United Arab Emirates. Our results are consistent with those of Guo et al (2016), as these authors mentioned the failure of the chloroplast genes rbcL and matK in plant specimens identification.…”
Section: Discussionmentioning
confidence: 99%
“…PCRs of rbcL and matK markers for the chloroplast genome were amplified following the method described by Maloukh et al (2017), using a total volume of 50 µL, including 25 µL of Taq PCR Master Mix, 22 µL of distilled water, 1 µL of forward primer, 1 µL of reverse primer and 1 µL of the DNA template (50 -80 ng/µL). Amplification was performed in a Veriti 96-Well Fast Thermal Cycler (Applied Biosystems, CA, USA), with an initial denaturation at 94°C for 3 min.…”
Section: Dna Amplification and Sequencingmentioning
confidence: 99%